2016
DOI: 10.1016/j.cortex.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep not just protects memories against forgetting, it also makes them more accessible

Abstract: In press at Cortex 2 AbstractTwo published datasets (Dumay & Gaskell, 2007, Psychological Science; Tamminen, Payne, Stickgold, Wamsley, & Gaskell, 2010, Journal of Neuroscience) showing a positive influence of sleep on declarative memory were re-analyzed, focusing on the "fate" of each item at the 0-hr test and 12-hr retest. In particular, I looked at which items were retrieved at test, and "maintained" (i.e., not forgotten) at retest, and which items were not retrieved at test, but eventually "gained" at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 38 publications
7
65
2
Order By: Relevance
“…Here, we found that sleep after learning appeared to prevent decay of episodic memory for the newly learned items, and eventual sleep in the AM group arrested apparent decay, with some suggestion of improved recall to a level shown by the PM group. These findings are consistent with Dumay (2016), suggesting that sleep not only prevented forgetting but also improved access to previous encoded items (but cf. Schreiner & Rasch, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…Here, we found that sleep after learning appeared to prevent decay of episodic memory for the newly learned items, and eventual sleep in the AM group arrested apparent decay, with some suggestion of improved recall to a level shown by the PM group. These findings are consistent with Dumay (2016), suggesting that sleep not only prevented forgetting but also improved access to previous encoded items (but cf. Schreiner & Rasch, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…As the experimental induction of memory reactivations by memory cues should primarily impact a consolidation mechanism that is considered "active" (i.e., memory reactivations), our data provide a unique opportunity to test the conceptual assumption raised by Dumay (2015). The author argues that if behavioral gains indeed reflect an active and losses a passive memory mechanism, then cueing during sleep should primarily impact behavioral gains without significant effects on memory losses.…”
Section: A N U S C R I P Tmentioning
confidence: 86%
“…Still, there is an ongoing debate which processes are at the bottom of sleep's impact on memory processing: either a passive mechanism of protection from interference (Mednick, Cai, Shuman, Anagnostaras, & Wixted, 2011) or an active mechanism including information processing (Diekelmann & Born, 2010). Two recent studies (Dumay, 2015;Fenn & Hambrick, 2012) set out to shed light on this important issue and proposed a direct behavioral parameter, indicating either an active or passive memory mechanism during sleep: Behavioral memory gains vs. memory losses. Gained items are not remembered before, but only after the retention interval, whereas lost items are remembered before, but not after sleep and wakefulness.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They also add to a decade of studies showing all kinds of offline, mostly sleep-related, changes in the representation of newlylearnt words (e.g., Bakker, Takashima, van Hell, Janzen, & McQueen, 2015;Bowers et al, 2005;Dumay, 2016;Dumay & Gaskell, 2007Gaskell & Dumay, 2003;Leach & Samuel, 2007;Tamminen, Davis, & Rastle, 2015;see Kapnoula & McMurray, 2016, for an opposing view).…”
Section: Discussionmentioning
confidence: 99%